Spectroscopic evidence for a 5-coordinate oxygenic ligated high spin ferric heme moiety in the Neisseria meningitidis hemoglobin binding receptor - Mokry, David Z.; Nadia-Albete, Angela; Johnson, Michael K.; Lukat-Rodgers, Gudrun S.; Rodgers, Kenton R.; Lanzilotta, William N. (Biochimica et biophysica acta, 2014)
For many pathogenic microorganisms, iron acquisition represents a significant stress during the colonization of a mammalian host. Heme is the single most abundant source of soluble iron in this environment. While the importance of iron assimilation for nearly all organisms is clear, the mechanisms by which heme is acquired and utilized by many bacterial pathogens, even those most commonly found at sites of infection, remain poorly understood. An alternative protocol for the production and purification of the outer membrane hemoglobin receptor (HmbR) from the pathogen Neisseria meningitidis has facilitated a biophysical characterization of this outer membrane transporter by electronic absorption, circular dichroism, electron paramagnetic resonance, and resonance Raman techniques. HmbR co-purifies with 5-coordinate high spin ferric heme bound. The heme binding site accommodates exogenous imidazole as a sixth ligand, which results in a 6-coordinate, low-spin ferric species. Both the 5- and 6-coordinate complexes are reduced by sodium hydrosulfite. Four HmbR variants with a modest decrease in binding efficiency for heme have been identified (H87C, H280A, Y282A, and Y456C). These findings are consistent with an emerging paradigm wherein the ferric iron center of bound heme is coordinated by a tyrosine ligand. In summary, this study provides the first spectroscopic characterization for any heme or iron transporter in Neisseria meningitidis, and suggests a coordination environment heretofore unobserved in a TonB-dependent hemin transporter. A detailed understanding of the nutrient acquisition pathways in common pathogens such as N. meningitidis provides a foundation for new antimicrobial strategies. •Isolation of the Neisseria meningitidis outer membrane hemoglobin receptor (HmbR).•Preliminary spectroscopic characterization of Neisseria meningitidis HmbR.•Further evidence for oxygenic heme ligation in heme transfer by enteric pathogens.